Mentorship: New Outlines of Organization of Social Environment for Personnel Training and Development in the Large Industrial Companies - ЧеглаковаЛюдмила Михайловна (Journal of Economic Sociology, 2011)
The paper considers possibilities and problems of mentorship in the large industrial companies in Russia. Approaches to definitions of mentorship, its major functions in organizations and society are analyzed. Types and modifications of mentorship in contemporary Human Resource management and demands for their applications are systematized. Practical examples are used to demonstrate an effectiveness of mentorship in the business organizations. An experience of consulting projects is attracted to see how Programs of Mentorship are implemented at the Russian enterprises at present.